2016
DOI: 10.1097/bpb.0000000000000266
|View full text |Cite
|
Sign up to set email alerts
|

Modified Ponseti method of treatment for correction of neglected clubfoot in older children and adolescents – a preliminary report

Abstract: Congenital talipes equinovarus may be the most common congenital orthopedic condition requiring treatment. Nonoperative treatment including different methods is generally accepted as the first step in the deformity correction. Ignacio Ponseti introduced his nonsurgical approach to the treatment of clubfoot in the early 1940s. The method is reportedly successful in treating clubfoot in patients up to 9 years of age. However, whether age at the beginning of treatment affects the rate of effective correction and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 14 publications
2
20
0
Order By: Relevance
“…Most cases of untreated CC occur in developing countries, due to deficiencies in the local public health systems, whereby children are not adequately treated [ 24 ]. The deformity becomes worse when walking because the body weight falls on the lateral side of the foot, causing contracture of the medial tissues and plastic deformity of the bones [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cases of untreated CC occur in developing countries, due to deficiencies in the local public health systems, whereby children are not adequately treated [ 24 ]. The deformity becomes worse when walking because the body weight falls on the lateral side of the foot, causing contracture of the medial tissues and plastic deformity of the bones [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other options include tarsectomy, midfoot osteotomy, arthrodesis, and correction with a circular external fixator, among others [ 27 29 ]. This type of treatment demands commitment, the postoperative period is long [ 24 ], and the rate of complications and cost are high [ 30 ]. In addition, the result is often a painful foot in childhood [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies on the effectiveness of the Ponseti method for patients over age 1, but the early evidence has been promising. Studies in Brazil, Nepal, India and Ethiopia reported that use of the Ponseti method allowed for avoidance of soft tissue release in 66%-92% of cases above one year of age[ 8 - 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The initial deformities of clubfoot are worsened by secondary changes due to weight-bearing and walking of the children as the side or dorsum of the affected foot begins to bear the weight, causing local skin ulcers, callosities and bursae formation, medial soft tissue contracture, and plastic deformation of bones 4 . The NCF can impose a heavy physical, psychological, social, and economic burden on the patients, families, communities, and countries 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%